1989
DOI: 10.1577/1548-8446(1989)014<0022:eonafd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Extinctions of North American Fishes During the past Century

Abstract: Extinctions of 3 genera, 27 species, and 13 subspecies of fishes from North America are documented during the past 100 years. Extinctions are recorded from all areas except northern Canada and Alaska. Regions suffering the greatest loss are the Great Lakes, Great Basin, Rio Grande, Valley of Mexico, and Parras Valley in Mexico. More than one factor contributed to the decline and extinction of 82% of the fishes. Physical habitat alteration was the most frequently cited causal factor (73%). Detrimental effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
294
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(307 citation statements)
references
References 32 publications
4
294
0
9
Order By: Relevance
“…Whittier et al (1997) reported that piscivores, especially nonnative piscivores introduced to improve fishing, were associated with lower minnow species richness (lower IBI scores) in northeastern U.S. lakes. Many other authors have also raised concerns about the association of nonnative game fish-deliberately introduced to improve fisheries-with declines or extirpation of native fishes (e.g., Miller et al 1989;Rahel 2002;Sanderson et al 2009). Clearly, fishery quality is often a fundamentally different ecological endpoint or ecosystem service than fish assemblage condition as measured by an IBI or by native species richness.…”
Section: Discussionmentioning
confidence: 99%
“…Whittier et al (1997) reported that piscivores, especially nonnative piscivores introduced to improve fishing, were associated with lower minnow species richness (lower IBI scores) in northeastern U.S. lakes. Many other authors have also raised concerns about the association of nonnative game fish-deliberately introduced to improve fisheries-with declines or extirpation of native fishes (e.g., Miller et al 1989;Rahel 2002;Sanderson et al 2009). Clearly, fishery quality is often a fundamentally different ecological endpoint or ecosystem service than fish assemblage condition as measured by an IBI or by native species richness.…”
Section: Discussionmentioning
confidence: 99%
“…The major factors responsible for this rapid decline in freshwater species are physical alteration, habitat loss, water withdrawal, pollution, overexploitation and the introduction of non-native species (Sala et al, 2000;Millennium Ecosystem Assessment, 2005;Revenga et al, 2005). Habitat alteration is cited as a leading cause of extinction in general, and has contributed to 73% (Miller et al, 1989) of the fish extinctions in North America during the twentieth century (Allan and Flecker, 1993;Sala et al, 2000). In this study, focus is on the effects of catchment alteration and increasing nutrient concentrations on macroinvertebrate and fish biodiversity in rivers and streams.…”
Section: Introductionmentioning
confidence: 99%
“…river or lake basins) with very reduced ability for inter-basin movement (Hocutt and Wiley, 1986;Unmack, 2001), in contrast with the relatively free-moving marine fishes, lays in the base of the conservation problems of the former (Richter et al, 1997). The decline of freshwater fishes is a generalised phenomenon noticeable on global (Duncan and Lockwood, 2001;Cowx and Collares-Pereira, 2002), regional and local (Miller et al, 1989;Crivelli, 1996;Moyle and Randall, 1998;López-Rojas and Bonilla-Rivero, 2000) scales. The principal threats to freshwater fishes are the deterioration or destruction of habitats, both by pollution and intense modifications (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Species introductions have been frequently cited as an important threat to native freshwater fauna, including amphibians and fishes (Miller et al, 1989).…”
Section: Introduced Species Dams and Conservation Statusmentioning
confidence: 99%